Numerical study of unsteady casson fluid flow and heat transfer over a stretching surface with modified magnetic field effects - Iskandar, Waini; Nurul Amira, Zainal; Najiyah Safwa, Khasi’ie; Abdul Rahman, Mohd Kasim; Nurul Farahain, Mohammad (Centre for Advanced Research on Energy, 2018)
Numerical study of unsteady Casson fluid flow and heat transfer over a stretching surface with modified magnetic field effects is investigated. The governing partial differential equations are transformed into ordinary differential equations by using similarity transformation which then solved numerically by Keller box method. The validation process is conducted by comparing the present results to previous study. The effects of several parameters on the fluid flow and heat transfer are analysed and discussed. Results show that the increasing of Casson and aligned angle parameters suppressed the fluids velocity. Meanwhile, the unsteadiness parameter led to decrease the fluid temperature.